HUBUNGAN LAMA MENDERITA DIABETES MELITUS DAN KADAR GULA DARAH DENGAN KUALITAS HIDUP PADA PASIEN DIABETES MELITUS TIPE 2 - Nanang Priambodo; Rina Kriswiastiny; Dita Fitriani (Medula, 2023)
Diabetes Mellitus is a metabolic disorder with a marked high level of glucose in the blood. Diabetes mellitus can affect the quality of life of patients because diabetes mellitus will accompany a lifetime of patients with diabetes mellitus, if the treatment done to patients with diabetes mellitus is not appropriate. to determine the relationship between long-suffering from diabetes mellitus and blood sugar levels with quality of life in patients with Type 2 diabetes mellitus. this research uses observational analytical method and with cross sectional approach. based on the results of this study found that the most respondents who have a good quality of life is from the old group suffering from Type 2 diabetes mellitus >10 years as many as 31 (55.4%) respondents, and from the group of blood sugar levels 140-200 mg/dl sebnyak 29 (56.9) respondents. there is a relationship between long-suffering from Type 2 diabetes mellitus with quality of life with the results of p-value = 0.000 (p<0.05). It is known that there is a relationship between blood sugar levels and quality of life with the results of p-value = 0.000 (p<0.05).